Microfinance Institutions and Credit Unions in Albania : Regulatory, Supervisory and Market Development Issues - World Bank (Washington, DC, 2013)
The objective of this report is to present an assessment of the current legal, regulatory, and supervisory framework in Albania for microfinance, as well as an assessment of institutions rendering microfinance services (MFIs), including the Savings and Credit Associations (SCAs) and credit unions (CUs), to identify future development priorities. Economic conditions have improved in Albania in recent years, but a significant percentage of the population is still considered below the poverty level. The report lists future development priorities for the SCAs and MFIs, emphasizing poverty reduction through microfinancing. Several MFIs, and one CU, expressed some desire to borrow from the World Bank. The report finds this promising, as long as it does not crowd out commercial sources that serve to integrate MFIs, CUs, and SCAs into the larger financial sector. The growth of SCAs might be enhanced by further consolidation of smaller SCAs into larger SCAs. Mergers based on joint objectives and bounds can expand the geographical coverage and clientele base, facilitate the increase of cash flows and access to capital, and achieve economies of scale in view of reducing fixed costs. Albania also wishes to obtain a banking license and focus exclusively on the microfinance market. A tax exemption enables CUs and SCAs to build up capital through retained earnings. Eliminating their tax exemption would either reduce their capital, or require that CUs replace the taxed earnings with other means of capitalization to maintain the same capital reserves. The report recommends that the Bank of Albania (BoA) should continue to work with the CUs on consolidating and strengthening the SCAs.